2016
DOI: 10.1108/ajim-03-2016-0031
|View full text |Cite
|
Sign up to set email alerts
|

Role of social media in information-seeking behaviour of international students

Abstract: Purpose-The purpose of this paper is to investigate the information-seeking behaviour of international students in terms of their information needs and to highlight the role of social media. Design/methodology/approach-In this paper, a systematic literature survey was conducted in order to investigate information-seeking trends among international students while using social media. As a result, an exhaustive systematic literature review (SLR) was carried out in order to investigate social media as a source for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 98 publications
(182 reference statements)
2
43
0
3
Order By: Relevance
“…Baris Horzum 2016; Chao & Keung 2017;García-domingom et al 2017) that established a positive and significant relationship between Facebook usage and information search. Also, the existing literature on students' use of SNSs shows that students use SNSs like Facebook, Twitter and Instagram to search for information which enables them to adapt to new environments (Hamid et al 2016;Manjunatha 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baris Horzum 2016; Chao & Keung 2017;García-domingom et al 2017) that established a positive and significant relationship between Facebook usage and information search. Also, the existing literature on students' use of SNSs shows that students use SNSs like Facebook, Twitter and Instagram to search for information which enables them to adapt to new environments (Hamid et al 2016;Manjunatha 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Tse, Bridges and Srinivasan (2015) found that individuals use SNS to make inquiries about their health concerns. Similarly, a study carried out by Hamid et al (2016) revealed that international students use SNS to search for information which enables them to adapt to new environments. Students also use SNS to search for information related to their academic studies (Manjunatha 2013).…”
Section: The Need To Share and Search For Informationmentioning
confidence: 99%
“…In this respect, with providing entertaining shares, businesses should encourage liking and sharing of large number of individuals and be able to turn it into advantage (Schivinski and Dabrowski, 2015). Social media is becoming the newest and up-to-date source of information for customers (Hamid et al, 2016) because information is simultaneously shared in real time on the social media. Unlike traditional mass communication channels, social media facilitate the interaction, content…”
Section: Social Media Marketing Activitiesmentioning
confidence: 99%
“…Social media is presently being used as an information seeking medium despite its fundamental purpose that was essentially to support communication and social activities (Head and Eisenberg 2010;Head and Eisenberg 2011;Lenhart et al 2007;Noorhidawati et al 2015). This was evident by a few studies reported on the usage of social media as an information seeking tool such as by Abidin, Kiran and Abrizah (2013), Bilgihan, Peng and Kandampully (2014), Hamid et al (2016), Knight et al (2015), .…”
Section: Introductionmentioning
confidence: 94%